Strategi Distribusi Zakat dan Pemberdayaan Mustahik di LAZ Persis KLP Cipedes Tasikmalaya: Zakat Distribution Strategy and Mustahik Empowerment in LAZ Persis KLP Cipedes Tasikmalaya - Nursyifa Suryani (Department of Management Zakat and Waqf, 2024)
The purpose of this study is to find out about the strategy of distributing zakat funds by LAZ Persis KLP Cipedes Tasikmalaya in increasing mustahik empowerment in Cipedes District. This research method uses a qualitative descriptive approach and collects data using field research methods with data collection techniques through interviews. The results showed that the strategy of distributing zakat funds at LAZ Persis KLP Cipedes Tasikmalaya uses various work programs such as caring people, shaleh people, smart people, healthy people, and independent people and collaborates with various parties. However, the obstacle in distributing zakat funds lies in the regional apparatus in collecting data on zakat recipients because they do not meet the criteria as mustahik, so that the distribution of zakat funds is not on target and uneven. Therefore, there is a need for government intervention to strengthen the supervision system, improve transparency and optimize administrative processes in distributing zakat funds. This finding has implications so that the distribution of zakat funds can be carried out evenly and on target. Keywords: Strategy, Distribution, Zakat, Mustahik